A new miniature species, Bulbophyllum nghiasonii, sect. Brachyantha (Orchidaceae) from northern Vietnam - Dang, Minh Quan; Averyanov, Leonid V.; Dang, van Son; Bui, van Huong; Amsler, Roland; Maisak, Tatiana; Truong, Ba Vuong (Phytotaxa, 2021)
The new species discovered in Thanh Hoa Province of northern Vietnam described here as a new species for science. It is similar to B. muscicola but differs in smaller habit, inflorescence shorter than leaves, shorter lateral sepals with unequally lobed blunt apex, and slender stelidia. The newly described species also can be compared with B. japonicum but it differs in the size and shape of leaves, tepals, and lip. Detailed morphological description, illustration, data on distribution, and phenology of the new species are presented.